2013
DOI: 10.1021/ef302195c
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Autoignition Trends in Butanol Isomers at Elevated Pressure

Abstract: Autoignition experiments of stoichiometric mixtures of s-, t-, and i-butanol in air have been performed using a heated rapid compression machine (RCM). At compressed pressures of 15 and 30 bar and for compressed temperatures in the range of 715−910 K, no evidence of a negative temperature coefficient region in terms of ignition delay response is found. The present experimental results are also compared with previously reported RCM data of n-butanol in air. The order of reactivity of the butanols is n-butanol>s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 36 publications
10
70
0
Order By: Relevance
“…The volume traces were determined from the measured pressure trace of the non-reactive experiment using isentropic core relations and a temperature-dependent mixture specific heat ratio [31]. Details on compositions and volume histories can be found in Supplementary…”
Section: Simulations and Sensitivity Analysismentioning
confidence: 99%
“…The volume traces were determined from the measured pressure trace of the non-reactive experiment using isentropic core relations and a temperature-dependent mixture specific heat ratio [31]. Details on compositions and volume histories can be found in Supplementary…”
Section: Simulations and Sensitivity Analysismentioning
confidence: 99%
“…In this approach, continuous stirring is needed to ensure a homogeneous mixture, for instance by using a magnetic stirrer [cf. 44,65,[70][71][72][73][74][75]. In addition, the possibility of fuel cracking/pyrolysis within the mixture preparation vessel over an extended time period needs to be avoided, and characterization experiments should be conducted to confirm the assumptions of minimal/negligible fuel loss, mixture homogeneity, and non-decomposition of fuel in the mixture preparation vessel, as carried out in [e.g., 65,73,74].…”
Section: Uncertainties and Issues For Rcm Experimentsmentioning
confidence: 99%
“…Experiments have also been performed in rapid compression machines, although the acquired ignition delay times [20] reaction network for iso-butanol oxidation, especially the pathways involving oxygen addition to fuel radicals [22]. No speciation studies have been reported at high pressures and low to intermediate temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…No speciation studies have been reported at high pressures and low to intermediate temperatures. Weber and Sung [20] commented that none of the existing models can predict the ignition delays at high pressure (30 bar) and low to intermediate temperature (754-857 K) well, and highlighted the importance of the peroxy chemistry in the low temperature pathways of iso-butanol oxidation based on sensitivity analysis of the ignition delay time using the Sarathy mechanism [17]. Without intermediate species information, the competing ratios between β-scission reactions and fuel propagation into the low temperature chain branching pathway of oxygen addition to fuel radicals were not investigated directly.…”
Section: Introductionmentioning
confidence: 99%